Design of drive stage of a Mosfet SiC converter - Guinard, Orianne (My University, 2014)
This thesis is about studying the gate driving of a Mosfet. One step was to build a new circuit board for this investigation using the software Target. First experiments were made that aim to test the driving circuit using an R,C load instead of a Mosfet. When comparing with the simulation, it appears that the gate driver operates as quick and normal as expected when it is used with an R,C load unless R and C are very small (smaller than what it would be using a Mosfet). However, when it is connected to a Mosfet and an R,L load, it doesn't react as fast as expected with the increasing drain-source voltage. Finally, the last part but not the least of this project consists of investigating the switching losses in a Mosfet and an SiC Mosfet. The result are not conclusive so far since the current measurement is biased.
Keywords: Energi; Elkraftteknik; Energy; Electric power engineering